МОБІЛЬНИЙ І ІНТЕЛЕКТУАЛЬНИЙ ПРИСТРІЙ ДЛЯ ІНДИВІДУАЛЬНОЇ ЛОГОПЕДИЧНОЇ ТЕРАПІЇ - Ungurean, Ioan (Vinnytsia National Technical University, 2013)
An expert system for customized logopedic therapy must allow the training of children depending on its speech disabilities and former progress. The children’s training is accomplished using exercises chosen by the expert system and can be performed either in the doctor’s office or at home for each child using an intelligent mobile device. The expert system generates a set of exercises for each child depending on the doctor’s recommendation. These exercises are transferred from PC to mobile devices using a Universal Serial Bus connection. The mobile device saves the result of each therapy session and when it is connected to PC it transfers the results to the expert system for analysis. Using the results of these analyses the expert system will decided whether a new session is needed and if that is the case, compute a new set of exercises.